On collateral: Implications for financial stability and monetary policy - Stefano Corradin; Marie Hoerova; Florian Heider (European Central Bank (ECB), 2017)
This paper examines the role of collateral in the financial system, with special emphasis on the implications for financial stability and the conduct of monetary policy. First, we review what drives the demand and supply for both real and financial collateral assets. Then we examine financial stability issues and the case for regulating the use of collateral. We discuss the role and design of market infrastructures such as central clearing counterparties (CCPs). Finally, we examine the interaction of standard and non-standard monetary policy and the functioning of private collateralised markets. We show that the use of collateral is neither a sufficient nor a necessary condition for financial stability. To ensure the stability of collateralised markets a mix of micro- and macro-prudential regulation, as well as a sufficient supply of safe public assets that can be used as collateral, are needed.
Keywords: E59; E44; G18; 330; Repo; haircuts; margins; central-clearing counterparties; central bank policies